A FRAMEWORK FOR DIAGNOSE DIABETES THROUGH PROTOTYPE SYSTEM - THANGARASU, GUNASEKAR (2016)
The clinical database has an extensive amount of information. The database usually contains doctor's counsel. results of clinical examinations, patient history and clinical symptoms of various types of biochemical data that physician considers in order to grasp a final diagnostic decision. Each type of data must be evaluated ffom the clinical database and assigned to a particular pathology during the diagnostic process for getting precise information about the disease. The clinical databases are widely utilized by several researchers with various diagnosing techniques for predicting different diseases.